Effects of 4G 2100 MHz Radiation on Lymphocyte Levels: An Experimental Study in Wistar Rats - Nafiisah Nafiisah; Fatiha Sri Utami Tamad; Nur Signa Aini; Ika Murti Harini; Tendi Novara (RSUP Dr. Kariadi, 2025)
BACKGROUND: Electromagnetic radiation (EMR) from mobile phones has become a global concern due to its potential impact on the immune system. However, the effects of EMR on lymphocyte levels remain inconsistent across studies. AIMS: This study aimed to evaluate the effects of 4G 2100 MHz EMR exposure on lymphocyte levels in Wistar rats. METHOD: This research employed a true experimental design with a Post Test Only Controlled Group Design. Four groups of male Wistar rats were used: a control group (G1) and three exposure groups subjected to EMR for 15 (G2), 30 (G3), and 45 days (G4). The exposed groups were subjected to 2 hours per day of 4G 2100 MHz EMR using a Redmi A2 mobile phone in WhatsApp call mode. Lymphocyte levels were analyzed using ANOVA to determine differences among the groups. RESULT: The average lymphocyte levels in groups G1, G2, G3, and G4 were 68.92 ± 4.78%, 63.37 ± 6.29%, 67.00 ± 11.51%, and 64.35 ± 13.58%, respectively. Statistical analysis revealed no significant differences among the groups (p = 0.703). CONCLUSION: Exposure to 4G 2100 MHz EMR for 15–45 days did not significantly change lymphocyte levels in Wistar rats. These findings support the need for further studies to evaluate other immunological parameters and the long-term effects of EMR exposure.